BIOLEACHING FOR THE RECOVERY OF METALS PEMISAHAN UNSUR LOGAM DENGAN BIOLEACHING - Susilawati, Rita (Buletin Sumber Daya Geologi, 2015)
A simple laboratory experiment has been conducted in order to demonstrate the ability of bacteria to leach the metal elements from insoluble ores or solid substrates. The experiment was conducted in a leaching column that was set up using 5 cc syringe that contained 1 cc of glass wool and 3.5cc of mine tailings. The basal salt was used as an inoculation media while mine tailing was used as a leaching subject and a source of bacterial leaching. Bacterial leaching was isolated using the most probable number (MPN) technique. Overall, the results of the experiment showed the capability of bioleaching process to recover metals from the mine tailings.